STUDENTS' PERCEPTION OF THE IMPLEMENTATION OF SYNCHRONOUS AND ASYNCHRONOUS LEARNING MODES - Apriana Apriana; Lesi Anggraini (Atthiflah: Journal of Early Childhood Islamic Education, 2023)
This research aimed to determine students' perceptions on the implementation of synchronous and asynchronous e-learning mode in the learning process at the second semester students at the Civil Engineering study program ITPA Pagar Alam. This research was a descriptive research involving students in academic year of 2022/2023 from one class consisting of 19 students. The data were taken using a triangulation technique. The data obtained were analysed qualitatively. The results of this research indicate that the students have perception of the implementation of the synchronous and asynchronous e-learning mode. The synchronous online learning mode has been implemented by using Zoom Meeting, Asynchronous online learning has been implemented by using an Email. The data obtained from the documentation, observation and interview showed that most students gave the responses to synchronous and asynchronous and advantages both two learning modes. This researched was conducted at the second semester students at the civil engineering study program Pagar Alam Institute of Technology. These findings were expected to be taken into consideration to know the advantages of synchronous and asynchronous e-learning mode, especially at the second semester students at the civil engineering study program Pagar Alam Institute of Technology